The Influence of Principal Transformational Leadership and Organizational Climate On Teacher Performance At SMA Negeri 9 Manado - Valentin Glady Sumual; Joulanda Altje Meiske Rawis; Romi Junior Mongdong (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the influence of the principal's transformational leadership and organizational climate on teacher performance at SMA Negeri 9 Manado. This research uses a quantitative approach with a survey method. The population of the study consisted of 124 teachers, with a sample of 94 teachers determined using the Slovin formula. Data were collected through questionnaires that had been tested for validity and reliability, and then analyzed using multiple linear regression. The results showed that the principal's transformational leadership has a positive and significant effect on teacher performance with a t-value of 2.598 and a significance level of 0.011 (<0.05). Organizational climate also has a positive and significant effect on teacher performance with a t-value of 7.071 and a significance level of 0.001 (<0.05). Simultaneously, both variables have a significant effect on teacher performance with an F-value of 141.782 and a significance level of 0.001 (<0.05). The coefficient of determination (R²) value of 0.752 indicates that 75.2% of the variation in teacher performance is influenced by these two variables. It can be concluded that improving transformational leadership and a conducive organizational climate can enhance teacher performance.